2023
DOI: 10.1186/s12302-023-00734-3
|View full text |Cite
|
Sign up to set email alerts
|

The need for assessment of risks arising from interactions between NGT organisms from an EU perspective

Abstract: Background New genomic techniques (NGTs) allow new genotypes and traits to be developed in different ways and with different outcomes compared to previous genetic engineering methods or conventional breeding (including non-targeted mutagenesis). EU GMO regulation requires an assessment of their direct and indirect effects that may be immediate, delayed or cumulative. Such effects may also result from the interactions of NGT organisms simultaneously present in a shared receiving environment or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Thus, in most cases, the result of the first step of the CRISPR/Cas application is a transgenic plant which may show a broad range of unintended genetic changes, which may be different to those emerging from conventional breeding, as for example discussed by Latham et al, 2006 and more recently confirmed by Yue et al (2022) . As recently summarized by Koller et al (2023) , such effects may be linked to epigenetic regulation, the disruption of genes, position effects, open reading frames, the unintended introduction of additional genes, changes in gene expression, genomic interactions which can involve plant constituents, or plant composition and agronomic characteristics ( Forsbach et al, 2003 ; Makarevitch et al, 2003 ; Windels et al, 2003 ; Rang et al, 2005 ; Gelvin, 2017 ; Jupe et al, 2019 ; Liu et al, 2019 ; Chu and Agapito-Tenfen, 2022 ; Yue et al, 2022 ). There are several studies showing that the problem of unintended insertion of transgenes is relevant to NGT applications in plants ( Li et al, 2015 ; Braatz et al, 2017 ; Biswas et al, 2020 ; Michno et al, 2020 ) or also animals ( Norris et al, 2020 ).…”
Section: Five Categories Of Unintended Genetic Changes Resulting From...mentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, in most cases, the result of the first step of the CRISPR/Cas application is a transgenic plant which may show a broad range of unintended genetic changes, which may be different to those emerging from conventional breeding, as for example discussed by Latham et al, 2006 and more recently confirmed by Yue et al (2022) . As recently summarized by Koller et al (2023) , such effects may be linked to epigenetic regulation, the disruption of genes, position effects, open reading frames, the unintended introduction of additional genes, changes in gene expression, genomic interactions which can involve plant constituents, or plant composition and agronomic characteristics ( Forsbach et al, 2003 ; Makarevitch et al, 2003 ; Windels et al, 2003 ; Rang et al, 2005 ; Gelvin, 2017 ; Jupe et al, 2019 ; Liu et al, 2019 ; Chu and Agapito-Tenfen, 2022 ; Yue et al, 2022 ). There are several studies showing that the problem of unintended insertion of transgenes is relevant to NGT applications in plants ( Li et al, 2015 ; Braatz et al, 2017 ; Biswas et al, 2020 ; Michno et al, 2020 ) or also animals ( Norris et al, 2020 ).…”
Section: Five Categories Of Unintended Genetic Changes Resulting From...mentioning
confidence: 99%
“…In short, and as summarized also by Kawall (2019) and Koller et al (2023) , site directed nucleases (SDN), such as CRISPR/Cas (clustered regularly interspaced short palindromic repeats/CRISPR associated) ( Jinek et al, 2012 ), are highly relevant in this context: they are designed to target specific DNA sequences in the genome to knock out gene functions (i.e. SDN-1) or to introduce specific changes of particular nucleotides (i.e.…”
Section: Differences Between Genetic Changes Caused By Ngts and Conve...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thorough risk assessments need to be carried out in order to assess potential threats to the environment and public health. This involves determining whether the modified crops are allergenic and whether there may be unforeseen side effects [ 102 ]. It is important to put strategies like monitoring and containment measures into practice to lessen these risks.…”
Section: The Legal Ethical and Biosafety Concerns Of Using Transgenic...mentioning
confidence: 99%